Anmeldelser - Fock, Eva (Danish Yearbook of Musicology, 1994)
Review of: Morten Levy: The World of the Gorrlaus Slåtts. A Morphological Investigation of a Branch of Norwegian Fiddle Music Tradition. I-III + kassettebånd. (Acta Ethnomusicologica Danica, 6). København, Forlaget Kragen I989.